The Write Way Forward: Exploring the Impact of Mind Mapping on Academic Excellence - Munira Hasjim; Tadjuddin Maknun; Lukman Lukman; Muslimat Muslimat; Andi Agussalim; Zohrah Hasyim; Ermi Dyah Kurnia; Indarwati (Migration Letters, 2023)
One of the tasks that students must do as part of the learning process in higher education is scientific writing. However, many students still require assistance in producing high-quality writing. The thought mapping method is one method for improving the quality of student writing. The purpose of this study was to determine the efficacy of applying the mind mapping approach to improve the quality of student writing at Universitas Hasanuddin. An experimental approach using a pretest-posttest control group design mechanism was used in this investigation. The samples for this study came from the second semester of medical school at Universitas Hasanuddin. Class A was the controlled group, and Class B was the experimental group. There were 50 students in each class. The researcher used purposeful sampling. This research employed a quantitative methodology. Furthermore, the study’s design was quasi-experimental, and the instrument was a written test. To determine the instrument’s dependability, the researcher employed a scoring rubric, specifically analytic scoring, to rate the students’ writing on the pre-test and post-test. As a result, the experimental class’s pre-test mean score was 58.46, whereas the students’ post-test mean score was 85.20. On the contrary, the controlled class’s pre-test mean score was 59.54, while the post-test mean score was 62.84. The post-test mean score of the experimental class treated with the mind mapping approach demonstrated a substantial effect. It was higher than the post-test mean score of the controlled class that was not treated with the mind mapping approach. It demonstrated the effectiveness of the mind-mapping approach. In other words, adopting the mind mapping technique for student writing at Universitas Hasanuddin had a beneficial effect on the learning process in higher education.